Pendampingan Fasilitasi Pojok Baca sebagai Sarana Edukasi dan Peningkatan Literasi pada Pelajar di Desa Tewang Kadamba Kalimantan Tengah - Abi Umaroh; Erna Wijayanti; Abdul Malik; Moh. Masrur (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2024)
The lack of facilities and supporting resources for teaching and learning activities in educational institutions and places of worship in Tewang Kadamba Village is a major factor hindering the development of students' literacy skills. In fact, literacy skills are one of the most fundamental aspects that every student must possess to support their continuity as individuals who are expected to live intelligently and with character. One of the breakthroughs offered by the researchers to solve the question as intended is by organizing a reading corner facilitation and facilitation to support the literacy skills of students in the Tewang Kadamba village. Therefore, this research is aimed at evaluating the effectiveness of the reading corn facilitation as a means of education and literacy improvement for students in Tewang kadamba village, central Kalimantan. The qualitative descriptive method was chosen to gain a deep understanding of the social, cultural, and historical context of a phenomenon. The research results show that reading corners can be an effective strategy to increase students' reading interest. Through three stages, namely planning, implementation, and evaluation, the provision of reading corner facilities has proven to enhance the love of reading and change students' positive attitudes towards literacy culture, both at school and in places of worship.